EFEKTIFITAS METODE GILLINGHAM UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KESULITAN BELAJAR KELAS III SD N 01 LIMAU MANIS PADANG - A Rahim Kurniawan Anwar (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstract: This research is motivated by problems in a child's learning difficulties in SDN 01 Class III Sweet Lemons who have difficulty in reading the beginning so that even if the child is in class III he was not able to read well. Under these conditions, the researchers want to prove that the use of Gillingham method can boost children's reading skills beginning in third grade learning difficulties in SDN 01 Limau Manis. This study uses a Single Subject Research approach, with desian  A –B- A and data analysis techniques using visual analysis chart. fungtions this study indicate that Gillingham method is able to improve the reading skills of learning difficulties for children beginning Grade III Sweet  SDN 01  Limau Manis Padang Kata Kuci :Kesulitan Belajar ; kemampuan ; Membaca ; Gillingham